The Therapeutic Role of Rho Kinase Inhibitor, Fasudil, on Pulmonary Hypertension; a Systematic Review and Meta-Analysis - Abedi, Farshad; Omidkhoda, Navid; Arasteh, Omid; Ghavami, Vahid; Hosseinzadeh, Hossein (Drug Research, 2022)
Background Pulmonary hypertension (PH) is a pathophysiological disorder, which involves multiple clinical conditions such as the upregulation of the Rho/ROCK signaling pathway. On the other hand, fasudil as a Rho kinase inhibitor has been investigated in the treatment of PH in some clinical studies.Objectives The present systematic review and meta-analysis aimed to evaluate the human clinical trials regarding the efficacy of fasudil in the management of PH.Methods Databases were searched with pre-defined search terms, up to December 2021. Efficacy measures were such as mean pulmonary arterial pressure (mPAP), systolic PAP (sPAP), pulmonary vascular resistance (PVR), systolic vascular resistance (SVR) and cardiac index (CI).Results A total of 12 studies involving 575 PH patients were included in our research. Eight short-term trials and four mid-term trials were found (no clinical trials on the long-term effects). Short-term trials had a before-after study design and measuring pulmonary hemodynamic parameters’ intervention revealed a statistically significant improvement of mPAP, sPAP, PVR, SVR, and CI in the meta-analysis of five eligible studies. Three mid-term trials also revealed improvement in some pulmonary hemodynamic parameters with fasudil and in another mid-term trial, fasudil significantly decreased rehospitalization and mortality in PH patients. No serious adverse effects with fasudil were reported in these trials.Conclusion Fasudil therapy is efficacious and probably safe in the improvement of some hemodynamics in PH patients along short and mid-term periods. However, long-term randomized controlled trials comparing fasudil with placebo and other treatments are warranted for confirmation of these benefits.
Keywords: Rho kinase inhibitor; Fasudil; Pulmonary hypertension; Meta-analysis